On the Origin and Evolutionary Relationships of the Reverse Transcriptases Associated With Type III CRISPR-Cas Systems - Toro, Nicolás; Martínez-Abarca, Francisco; González-Delgado, Alejandro; Mestre, Mario Rodríguez (Frontiers in Microbiology, 2018)
Reverse transcriptases (RTs) closely related to those encoded by group II introns but lacking the intron RNA structure have been found associated with type III clustered regularly interspaced short palindromic repeats (CRISPR)-Cas systems, a prokaryotic immune system against invading viruses and foreign genetic elements. Two models have been proposed to explain the origin and evolutionary relationships of these RTs: i) the “single point of origin” model, according to which these RTs originated from a single acquisition event in bacterial, with the various protein domains (RT, RT-Cas1 and Cas6-RT-Cas1 fusions) corresponding to single points in evolution; and ii) the “various origins” model, according to which, independent acquisition events in different evolutionary episodes led to these fusions. We tested these alternative hypotheses, by analyzing and integrating published datasets of RT sequences associated with CRISPR-Cas systems and inferring phylogenetic trees by maximum likelihood (ML) methods. The RTs studied could be grouped into 13 clades, mostly in bacteria, in which they probably evolved. The various clades appear to form three independent lineages in bacteria and a recent lineage in archaea. Our data show that the Cas6 domain was acquired twice, independently, through RT-Cas1 fusion, in the bacterial lineages. Taken together, there more evidence to support the “various origins” hypothesis.